2001
DOI: 10.1161/01.hyp.37.4.1124
|View full text |Cite
|
Sign up to set email alerts
|

Lacidipine Prevents Endothelial Dysfunction in Salt-Loaded Stroke-Prone Hypertensive Rats

Abstract: Abstract-Endothelium-dependent vasorelaxation is defective in hypertensive rats, especially in conduit arteries. In the stroke-prone spontaneously hypertensive rat, impaired endothelium-dependent vasorelaxation appears to contribute to the pathogenesis of stroke independent of blood pressure. Because treatment with lacidipine, a long-acting calcium channel blocker, protects against stroke and cardiovascular remodeling in this model, we investigated the effect of this treatment on endothelium-dependent vasorela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…Lacidipine is a calcium-channel blocker of the dihydropiridine class that has been shown to prevent endothelial dysfunction in hypertensive rats (38), restore endotheliumdependent vasodilation in hypertensive patients (39), and decrease oxidative stress (19). In this study, lacidipine reduced endothelin and malondialdehyde production and increased intracellular glutathione levels, although none of the effects induced by exposure of endothelial cells to ethanol were corrected.…”
Section: Discussionmentioning
confidence: 65%
“…Lacidipine is a calcium-channel blocker of the dihydropiridine class that has been shown to prevent endothelial dysfunction in hypertensive rats (38), restore endotheliumdependent vasodilation in hypertensive patients (39), and decrease oxidative stress (19). In this study, lacidipine reduced endothelin and malondialdehyde production and increased intracellular glutathione levels, although none of the effects induced by exposure of endothelial cells to ethanol were corrected.…”
Section: Discussionmentioning
confidence: 65%
“…Statistical analysis was performed by ANOVA, followed by Fisher's PLSD test; ‫,ء‬ P Ͻ 0.05 versus control. 1994) and in salt-loaded stroke-prone SHRs (Krenek et al, 2001). Furthermore, chronic nifedipine treatment causes an increase in expression of eNOS messenger RNA in the aorta from stroke-prone SHRs (Naruse et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in salt-loaded SHRSP demonstrated that inhibition of NO generation with NOS blockers abolishes Ach-stimulated responses, indicating that Ach-mediated vasodilation depends on endothelium-derived NO in this model. 31 Endothelium-independent relaxation was assessed in norepinephrine-precontracted vessels exposed to sodium nitroprusside ( …”
Section: Study Of Small Arteriesmentioning
confidence: 99%